Successful Handling of Disseminated BCG Disease in a Child with Severe Combined Immunodeficiency - Sílvia Bacalhau; Cristina Freitas; Rosalina Valente; Deolinda Barata; Conceição Neves; Katrin Schäfer; Annelie Lubatschofski; Ansgar Schulz; João Farela Neves (Case Reports in Medicine)
In high-burden countries, Mycobacterium bovis Bacillus Calmette-Guérin (BCG) vaccine is administered in newborn to prevent severe Mycobacterium tuberculosis infection. Because life-threatening disseminated BCG disease may occur in children with primary immunodeficiency, vaccination strategy against tuberculosis should be redefined in non-high-burden countries. We report the case of a patient with X-linked severe combined immunodeficiency (SCID) who developed disseminated BCG disease, highlighting the specific strategies adopted.